2009
DOI: 10.1016/j.ijimpeng.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction of dynamic composite material properties for hypervelocity impact simulations

Abstract: Recent advances in the description of fibre-reinforced polymer composite material behaviour under extreme loading rates provide a significant extension in capabilities for numerical simulation of hypervelocity impact on composite satellite structures. Given the complexity of the material model, extensive material characterisation is required, however, as the properties of composite materials are commonly tailored for a specific application, experimental characterisation is not efficient, particularly in prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…This gives the value of S ILSS ¼ 135 MPa. Second, Ryan et al [21] have shown that different types of CFRP systems reveal high level of similarity in their response to shock loading. Having this in mind, we adopted the values of A 2 ¼ A 3 ¼ 0 and B 0 ¼ B 1 ¼ 2:5 obtained experimentally in Ref.…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This gives the value of S ILSS ¼ 135 MPa. Second, Ryan et al [21] have shown that different types of CFRP systems reveal high level of similarity in their response to shock loading. Having this in mind, we adopted the values of A 2 ¼ A 3 ¼ 0 and B 0 ¼ B 1 ¼ 2:5 obtained experimentally in Ref.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…Having this in mind, we adopted the values of A 2 ¼ A 3 ¼ 0 and B 0 ¼ B 1 ¼ 2:5 obtained experimentally in Ref. [21] for UMS2526/Krempel carbon fiber reinforced plastic.…”
Section: Materials Propertiesmentioning
confidence: 99%
“…An orthotropic material typically provides data for the pressure as a function of volumetric and deviatoric response, which is commonly written using a polynomial EOS (Ryan et al 2009) as in Eqn 37:…”
Section: Composite Material: Gfrpmentioning
confidence: 99%
“…(9). Equations (3) and (9) are the key of Huang's elastoplastic micromechanics model, which has been validated by many researchers [32][33][34] . In this work, the Huang's two-phase bridging model is employed to establish the three-phase bridging model.…”
mentioning
confidence: 95%
“…are, respectively, elastic and plastic parts of the compliance matrix, whose expressions are shown in Eqs. (32)(33)(34). In plastic deformation, the Poisson's ratio t m υ can be set as 0.5, according to the non-compressive law.…”
mentioning
confidence: 99%